Investigation of the Possible Association Between Galectin and Apoptosis in Gastric Cancer Patients: Galectin and Apoptosis in Gastric Cancer Patients (Journal of Basic and Applied Research in Biomedicine, 2023)
Cancer is a type of disease that occurs as a result of the uncontrolled growth of cells, which has been very common in recent years, and some species have a poor prognosis. Galectin-3 is a multifunctional protein and is associated with the developmental process of tumors, including cell growth, adhesion, proliferation and metastasis. Galectin-3 has a broad effect on tumor development, including cell proliferation, apoptosis, cell adhesion, invasion, angiogenesis, and metastasis. Members of the BCLF-2 family are anti-apoptotic molecules required for the proteolytic degradation of the cell by caspases, which is the ultimate drive of programmed cell death, which plays a very important role in the regulation of the apoptotic pathway, ensures the integrity of the mitochondrial membrane and prevents the release of cytochrome C from the mitochondria. NF-kB, which is one of the important factors in cancer formation, is found in the cytoplasm, and there is a correlation between the protein levels of proinflammatory cytokines such as interlukin (IL)-1b, and IL-8, and the high incidence of cancer.  There are two types of apoptotic caspases: initiator (apical) caspases and effector (executioner) caspases. Initiator caspases (e.g., caspase-2, -8, -9 and -10) cleave inactive pro-forms of effector caspases, thereby activating them. Effector caspases (e.g., caspase-3, -6, -7) in turn cleave other protein substrates within the cell resulting in the apoptotic process. At least fourteen caspases have so far been implicated in human apoptotic pathway cascade. Among these, caspase-3 is considered to be a major executioner protease in apoptosis. To examine this mechanism in more detail, we aimed to examine the difference between Galectin, BCLF-2, Kaspase3, Kaspas 8, Nfkb levels before and after treatment in operable gastric cancer patients with the Elisa test. In this study, We observed a statistical increase in Galectin, BCLF-2, Kaspase3, Kaspas 8, Nfkb levels when the control group was compared with the preoperative group. There was a statistically significant increase in Galectin, BCLF-2, Nfkb, Caspase3, Caspase 8 levels in the preoperative group compared to the control. There is a statistical increased in Galectin, BCLF-2, Kaspase3, Kaspas 8, Nfkb levels in the postoperative group compared to the control. Although there was no statistical difference in Galectin, BCLF-2, Caspase-3, Caspase-8, Nfkb levels between pre and postoperative groups, a significant decrease was observed in Galectin, BCLF-2, Nfkb levels. A very slight increase was observed in Caspase-3 and Caspase-8 levels. In conclusion, we think that Galectin-3 Bcl-2 and NF-kB may be markers for gastric cancer patients. We think that it is appropriate to conduct this study with more patient groups and a longer period.